BRS Harmonia - triticale cultivar - Alfredo do Nascimento Junior; Manoel Carlos Bassoi; Márcio Só e Silva; Eduardo Caierão; Martha Zavariz de Miranda (Crop Breeding and Applied Biotechnology, 2015)
The triticale cultivar BRS Harmonia has moderate resistance to leaf rust, is outstanding in grain yield and quality, and its flour is suitable for cookie baking. It is an excellent alternative as winter crop for the different grain production systems in southcentral Brazil.